The Structure of Coronal Mass Ejections Recorded by the K-Coronagraph at Mauna Loa Solar Observatory - Hongqiang Song; Leping Li; Zhenjun Zhou; Lidong Xia; Xin Cheng; Yao Chen (The Astrophysical Journal Letters, 2023)
Previous survey studies reported that coronal mass ejections (CMEs) can exhibit various structures in white-light coronagraphs, and ∼30% of them have the typical three-part feature in the high corona (e.g., 2–6 R _⊙ ), which has been taken as the prototypical structure of CMEs. It is widely accepted that CMEs result from eruption of magnetic flux ropes (MFRs), and the three-part structure can be understood easily by means of the MFR eruption. It is interesting and significant to answer why only ∼30% of CMEs have the three-part feature in previous studies. Here we conduct a synthesis of the CME structure in the field of view (FOV) of K-Coronagraph (1.05–3 R _⊙ ). In total, 369 CMEs are observed from 2013 September to 2022 November. After inspecting the CMEs one by one through joint observations of the Atmospheric Imaging Assembly, K-Coronagraph, and LASCO/C2, we find 71 events according to the criteria: (1) limb event; (2) normal CME, i.e., angular width ≥30°; (3) K-Coronagraph caught the early eruption stage. All (or more than 90% considering several ambiguous events) of the 71 CMEs exhibit the three-part feature in the FOV of K-Coronagraph, while only 30%–40% have the feature in the C2 FOV (2–6 R _⊙ ). For the first time, our studies show that 90%–100% and 30%–40% of normal CMEs possess the three-part structure in the low and high corona, respectively, which demonstrates that many CMEs can lose the three-part feature during their early evolutions, and strongly supports that most (if not all) CMEs have the MFR structures.